La forma in movimento : Il corpo dell'attore nella tradizione scoliastica - Marinelli, Manlio (2024)
This paper analyzes and aims to highlight the gestures and bodily strategies of the tragic actor as the scholia describe them to the reader. According to them, tragic actors used strategies and patterns that not only had semantic valences but also brought into play specific skills to provoke the emotions of spectators. The article aims to argue that Hellenistic scholars observed the performers' bodily strategies without prejudice regarding the actors' dominance in achieving tragic effects. Certainly, it must be kept in mind that these sources deal with performances dating back to the fifth century: the memory of ancient scholarship is part of the way in which the tragic phenomenon is considered. This article is not about performance but about its memory.
Questo articolo analizza e si propone di evidenziare i gesti e le strategie corporee dell'attore tragico così come gli scoli li descrivono al lettore. Secondo loro, gli attori tragici utilizzavano strategie e schemi che non solo avevano valenze semantiche ma mettevano in gioco anche abilità specifiche per provocare le emozioni degli spettatori. L'articolo si propone di sostenere che gli studiosi ellenistici osservavano le strategie corporee degli artisti senza pregiudizi riguardo al dominio degli attori nel raggiungimento degli effetti tragici. Certamente bisogna tenere conto che queste fonti trattano di rappresentazioni risalenti al V secolo: la memoria dell'erudizione antica rientra nel modo in cui viene considerato il tragico fenomeno. Questo articolo non riguarda le prestazioni ma la sua memoria.
Keywords: Gestures; Body Strategies; Tragic Emotions; Scholia; Gesti^lit; Strategie corporee; Emozioni tragiche; Scoli